Advances on potential-driven growth of metal crystals from ionic liquids. Issue 4 (November 2022) - Islam, Md. Mominul; Ahmed, Saika; Miran, Muhammed Shah; Susan, Md. Abu Bin Hasan
Abstract: This article highlights the electrodeposition of metals, in crystalline or amorphous form, that are monentous in the present era of science and technology. Available literature related to nucleation and growth of metal crystals has been reviewed to gain insight into the mechanism and kinetics. The progress made in the electrodeposition technique, using an ionic liquid (IL) medium, has been detailed for selected metals using different ILs for achieving the controlled growth mechanism driven by electrochemical potential. Theoretical models for nucleation and growth of crystals by electrodeposition have been explained and the effect of crystallization overpotential on the growth of crystal growth has been discussed. Finally, the factors affecting the growth process and the mechanism have been identified and critically analyzed based on the available literature, fundamental knowledge-base, chemistry of ILs, and electrodeposition.